1994
DOI: 10.1577/1548-8659(1994)123<0482:agamos>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Age, Growth, and Mortality of Spotted Seatrout in Florida Waters

Abstract: Estimates of age, growth, and mortality of spotted seatrout Cynoscion nehulosus were made by analyzing fish from commercial and recreational catches in 1986-1988 in three estuarine areas of Florida: Apalachicola Bay, Charlotte Harbor, and Indian River Lagoon. Thin sections of sagittae were used to determine age: annulus formation occurred in November-May. The maximum observed age differed among areas, ranging from 5 to 9 years for males and from 6 to 8 years for females. Spotted seatrout reached 301-337 mm tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
36
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 15 publications
9
36
1
Order By: Relevance
“…Spotted seatrout from Florida demonstrated much faster growth (Murphy and Taylor 1994) than we found for sand seatrout. Spotted seatrout length at age 1 yr ranged from about 100 mm to nearly 200 mm greater than sand seatrout at age 1 yr, depending upon the sex of the fish and the estuary sampled.…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…Spotted seatrout from Florida demonstrated much faster growth (Murphy and Taylor 1994) than we found for sand seatrout. Spotted seatrout length at age 1 yr ranged from about 100 mm to nearly 200 mm greater than sand seatrout at age 1 yr, depending upon the sex of the fish and the estuary sampled.…”
Section: Discussioncontrasting
confidence: 52%
“…Length-atage of sand sea trout was quite variable between individuals, but within the limits previously ITported for this species (Shlossman, 1980). Other closely related species, such as spotted seatrout (Murphy and Taylor, 1994) and weakfish (Lowerre-Barbieri et al, 1995), have also shown great variability at age. The protracted spawning period that these species have has been recognized as a factor contributing to wide variability in length-at-age (Lowerre-Bar-bieri eta!., 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately nearly all published studies on sciaenid age and growth have reported percentage agreement as a measure of ageing precision. Published values of percentage agreement for temperate and subtropical sciaenids are: 88-99.8% for Cynoscion nebulosus (Murphy and Taylor, 1994;Nieland et al, 2002), 99-100% for Cynoscion regalis (Lowerre- Barbieri et al, 1994), 99% for Micropogonias undulatus , 90-92% for Micropogonias furnieri (ManickchandHeileman and Kenny, 1990), 92% for Pogonias cromis (Beckman et al, 1990), and 96-100% for Sciaenops ocellatus (Beckman et al, 1988;Murphy and Taylor, 1990;Ross et al, 1995;Murphy and Crabtree, 2001). Percentage agreement for the sectioned otoliths of U. canariensis used in this study was substantially less than these reported values, only, 43% agreement between the first and second reading rising to 80% agreement between the second and third reading.…”
Section: Discussionmentioning
confidence: 99%
“…First, female spotted seatrout experience high total mortality rates (67-75 % annually) because recreational anglers target larger (female) fish (Murphy and Taylor 1994;Nieland et al 2002). Therefore, by the end of each freshet period or 6-12 months post-release, only a portion of the 12-33 females released during each tagging event remained alive and available for detection.…”
Section: Sex-specific Avoidance Of Low Salinitiesmentioning
confidence: 99%